Green Energy Generated in Single-Chamber Microbial Fuel Cells Using Tomato Waste - Rojas-Flores, Segundo (2023)
This research used tomato waste as a substrate (fuel) in Single Chamber-Microbial Fuel Cells (scMFC) on a small scale. The electrochemical properties were monitored, the functional groups of the substrate were analyzed by Fourier Transform Infrared Spectrophotometry (FTIR) and a microbiological analysis was performed on the electrodes in order to identify the microorganisms responsible for the electrochemical process. The results show voltage peaks and an electrical current of 3.647 ± 0.157 mA and 0.957 ± 0.246 V. A pH of 5.32 ± 0.26 was measured in the substrate with an electrical current conductivity of 148,701 ± 5849 mS/cm and an internal resistance (Rint) of 77. 517 ± 8.541 Ω. The maximum power density (PD) displayed was 264.72 ± 3.54 mW/cm2 at a current density (CD) of 4.388 A/cm2. On the other hand, the FTIR spectrum showed a more intense decrease in its peaks, with the compound belonging to the phenolic groups being the most affected at 3361 cm−1. The micrographs show the formation of a porous biofilm where molecular identification allowed the identification of two bacteria (Proteus vulgaris and Proteus vulgaris) and a yeast (Yarrowia lipolytica) with 100% identity. The data found show the potential of this waste as a source of fuel for the generation of an electric current in a sustainable and environmentally friendly way, generating in the near future a mechanism for the reuse of waste in a beneficial way for farmers, communities and agro-industrial companies.